Study of the Effect of Local Raw Materials on the Physical and Mechanical Properties of Knitted Fabric (European Journal of Economics, Finance and Business Development, 2023)
In this article, using the capabilities of flat two-needle knitting machines, local raw materials were gradually introduced, i.e. the percentage of cotton thread in the knitted fabric, and the production technology was developed, its physical and mechanical parameters were studied. 3 samples of knitted fabric were taken, their technological indicators and physical and mechanical properties were experimentally studied, presented in a table and analyzed. Experimental samples knitted fabrics were designed and built on a LONG-XING LXA 252 12G flat-needle machine (China).